EFFECT OF STAKING METHODS ON THE GROWTH AND YIELD OF WATERMELON (CITRULLUS LANATUS) - Aderemi, T.F.; Aderemi, A.M.; Elesho, R.O.; Ayandokun, T.O.; Adewoye, A.A.; Adeniran, T.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
This study investigated the effect of staking methods on the vegetative growth and yield of watermelon (Citrullus lanatus, Thunb.) at the experimental plot of the Federal College of Forestry, Jericho, Ibadan, Nigeria. The treatment consisted of three (3) staking methods (staking (T1), no staking/ground trailing (T2) and trellis (T3)). These treatments were laid out in a Randomized Complete Block Design (RCBD) replicated three times. Growth parameters assessed at weekly intervals over twelve weeks includes: leaf count, leaf area (cm²), stem diameter (cm), stem length (cm), number of flowers, fruit count, and fruit weight (kg). Results of the experiment showed that, trellis-supported plants consistently outperformed the other treatments across all measured parameters. Trellis plants recorded the highest leaf count (115.74), leaf area (7.61 cm²), stem length (55.39 cm), flower number (23.81), fruit count (12.55), and fruit weight (0.95 kg). Ground-trailing plants generally recorded the lowest values. These findings indicated that trellis significantly enhances the vegetative growth and yield of watermelon and is recommended for adoption by farmers and agricultural practitioners in humid tropical environments.